MOTHERS' KNOWLEDGE AND ATTITUDES IN PREVENTING DIARRHEA IN TODDLERS AGED 1-5 YEARS IN SEI SERINDAN VILLAGE - Sari, Nova Luminda; S.KM, M.Epid, Wahidah; SST, M.KM, Ika Lestari Sitorus, (Cattleya Darmaya Fortuna, 2025)
WHO (World Health Organization) also states that malnutrition is a contributing factor to approximately 45.0% of all child deaths. Diarrhea is also primarily caused by contaminated food and drink sources. Based on the research results, 7 out of 9 mothers stated that they did not know how to prevent diarrhea in toddlers such as washing hands before giving food or drink, providing a regular diet, and maintaining toddler hygiene. And most mothers did not know how to treat their child with diarrhea, such as meeting body fluid needs, giving oral rehydration salts, getting enough rest, and consuming easily digestible foods. Diarrhea is the discharge of abnormal and liquid stools. Abnormal bowel movements and liquid stools with a frequency greater than usual (3 times or more than usual). The design of this study is descriptive, namely to describe how mothers' knowledge and attitudes in preventing diarrhea in toddlers aged 1-5 years and sampling using a total sampling method taken from all populations, namely 40 people. It is recommended that mothers in Sei Serindan village improve their knowledge and attitudes in preventing diarrhea in toddlers aged 1-5 years.